A Principal-Agent Model of Competition Law Compliance - Daniel Herold (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper analyzes firm owners' incentives to implement Competition Law Compliance Programs as imperfect monitoring devices in a principal-agent setup and the interaction effects with bonus contracts. The manager chooses working effort and has the option to cartelize. The model reveals a non-monotonic relationship between profit targets and incentives to collude. Contrary to intuition, it might be the case that low instead of high profit targets facilitate collusion. This result is driven by the threat of detection and punishment. A Compliance Program deters the agent from misbehavior and enhances effort as long as the agent did not engage in collusive activity. Additionally, the owner can use the Program as an insurance against fines.
Keywords: D21; D82; D02; 330